2013
DOI: 10.1186/1757-4749-5-35
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent post mortem changes in the composition of intestinal bacteria using real-time quantitative PCR

Abstract: Post mortem or even normal changes during life occurring in major gut bacterial populations are not known. We investigated Bacteroides sp., Bifidobacterium sp., Clostridium leptum, Clostridium coccoides, Streptococcus sp., Lactobacillus sp. and Enterobacteriacaea ratios in 7 fecal samples from healthy volunteers and in 61 autopsies rectum and cecum samples and studied the effect of post mortem time using quantitative real-time PCR. Bacterial ratios in stool samples from volunteers and rectum samples from autop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 17 publications
(17 reference statements)
2
20
0
Order By: Relevance
“…Tuomisto et al . 35 observed that the amount of bacterial DNA remained quite stable with time elapsed post-mortem, except for a substantial increase on day 5 post-mortem, during autopsies of rectum from male human. Those results indicated that the number of bacteria increased while the richness declined during the decomposition process.…”
Section: Discussionmentioning
confidence: 87%
“…Tuomisto et al . 35 observed that the amount of bacterial DNA remained quite stable with time elapsed post-mortem, except for a substantial increase on day 5 post-mortem, during autopsies of rectum from male human. Those results indicated that the number of bacteria increased while the richness declined during the decomposition process.…”
Section: Discussionmentioning
confidence: 87%
“…The fold value in target bacteria was calculated for each sample using the 2normalΔnormalΔCt method (Tuomisto et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…The threshold PCR cycle number (C t ) values were determined using the LIGHTCYCLER RELATIVE QUANTIFICATION software (Roche Applied Science, Mannheim, Germany). The fold value in target bacteria was calculated for each sample using the 2 ÀDDCt method (Tuomisto et al 2013).…”
Section: Faecal Microbiota Analysis By Real-time Pcrmentioning
confidence: 99%
“…Microorganisms exist both inside and outside the dead body and exhibit a distinct and temporal shift during the process of decay [22]. The gut, as an organ contains a large number of bacteria, and some bacteria have been shown to exhibit variations during the decomposition of corpses [11,23,24], which prompted this study. The bacterial communities in the decomposing rats showed a distinct shift in the categories and relative abundance compared with those in the living rats.…”
Section: Discussionmentioning
confidence: 99%